Factors associated with low back pain in air force fighter pilots: a cross-sectional study. Issue 4 (15th July 2021) - Gomes, Sâmara Raquel Alves; Mendes, P R F; Costa, L D O; Bulhões, L C C; Borges, D T; Macedo, Ld B; Brasileiro, J
Abstract : Introduction: Low back pain in military pilots is a frequent condition which constantly leads to absences from work, decreased concentration and performance during flight, as well as changes in work functions. Methods: This is a cross-sectional analytical study including 28 fighter pilots who underwent an evaluation comprising muscle strength and fatigue resistance, trunk mobility and application of questionnaires to identify associated clinical factors. Results: It was observed that 68% of the pilots reported low back pain with an average pain intensity of 3.7 at numerical pain scale in the last week. No significant differences were observed regarding the range of motion and trunk muscle strength when pilots with low back pain were compared with asymptomatic pilots. However, lateral right trunk muscle (mean difference=16, 95% CI 0.6 to 33.0]) and lateral left trunk muscle (mean difference=22, 95% CI 1 to 44) fatigue sooner in pilots with low back pain when the two groups were compared (p=0.04 for both). Conclusion: There was a high rate of low back pain complaints among fighter pilots. There was also a significant reduction in fatigue resistance of the lateral trunk muscles in symptomatic pilots when compared with asymptomatic pilots. These factors must be considered in the physical training of this population.